1983
DOI: 10.1007/bf02907768
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a carboxypeptidase from malted barley by affinity chromatography

Abstract: A carboxypeptidase was isolated from malted barley by affinity chromatography in a yield of approximately 30%. The specific activity was higher than previously obtained for similar enzymes. The enzyme was a dimer where each of the monomers consisted of two peptide chains linked by disulfide bridges. Each monomer contained a single suifhydryl group, which was inaccessible to p-hydroxymercuribenzoate and ELLMAN' S reagent when the enzyme was in its native state. The two peptide chains were separated and the N-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 47 publications
5
61
0
Order By: Relevance
“…Malt carboxypeptidase was isolated by affinity chromatography as previously described (5). All synthesized substrates were checked by HPLC as described in reference 22, and it was ascertained that the purity was higher than 98%.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Malt carboxypeptidase was isolated by affinity chromatography as previously described (5). All synthesized substrates were checked by HPLC as described in reference 22, and it was ascertained that the purity was higher than 98%.…”
Section: Methodsmentioning
confidence: 99%
“…3.4.16) from malted barley was described (5) and it was demonstrated that this enzyme exhibited activities similar to carboxypeptidase Y from baker's yeast, the most extensively characterized enzyme in this class (9,13). However, the carboxypeptidases from malt and yeast differ substantially with respect to molecular weight and other physical-chemical characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has not been established whether these carboxypeptidases represent isoenzymes. The carboxypeptidases isolated from germinated barley grains exhibit a similar complexity (11,28,37,135,154,190,200).…”
Section: Serine Earboxypeptidases In Higher Plantsmentioning
confidence: 99%
“…The amino acid composition of several serine carboxypeptidases has been determined (28,37,79,91,98,110,111,114,188,191) and it is characteristic that the enzymes isolated from fungi have much higher contents of the amino acids Asx and Glx and lower contents of the basic amino acids, i.e. Lys and Arg, than those from higher plants.…”
Section: Physico-chemical Properties Of Serine Carboxypeptidasesmentioning
confidence: 99%